"That's the whole idea of college readiness": A critical examination of universal Pre-K teachers' understandings around kindergarten readiness. (November 2020) - Akaba, Sanae; Peters, Lacey E.; Liang, Eva; Graves, Sherryl B.
Abstract: This study examines universal Pre-Kindergarten teachers' understanding of kindergarten readiness through critical lens towards neoliberal narratives of "quality and high return" (Moss, 2014; 2018) and power and knowledge that produce "regime of truth" (Foucault, 1984). In-depth, semi-structured interviews were conducted with 14 teachers, transcribed, and analyzed by utilizing thematic analysis. The implications include recognizing where the dominant narratives lie in early childhood education and valuing teachers, especially those of color, is critical to develop a clear definition of readiness with culturally relevant and sustainable approaches. (85) Highlights: Pre-K teachers recognize the need to conform to and have internalized the heightened demands and expectations. Pre-K teachers have adjusted their practice to demands on academic skills that intersect with their own teaching beliefs. Pre-K teachers' practices constantly change to align more to standards-based accountability and kindergarten readiness.